Aerodynamic Performance Analysis and Evaluation of NACA 653-218 Airfoiled Aircraft at Different Blended Winglet Configurations - Pant, T.R.; Shah, S.B.; Kshetri, M. (Kathmandu University Journal of Science, Engineering and Technology, 2021)
The research project explores specifically airfoiled (NACA 653-218) wing model for its aerodynamic performance, basically, the ratio of coefficient of lift to that of drag, on adapting a non-twisted classical winglet, also known by the name of Whitcomb (blended) winglet, by configuring its geometrical parameters. After reviewing the state-of-art of this technology used in modern aircrafts both in commercial/passenger and military, the only parameter that has significant influence on the particular results we were looking for, which is the increased CL/CD ratio relative to clean wing, was the cant angle of the winglet. When simulated using ANSYS Fluent solver, 3D-flow at the wingtip was visualized for both winglet and without winglet cases which showed the reduced intensity of the vortex at the tip, in the former case than the latter. Gain of 8-12% was found in CL/CD ratio in 30° canted winglet case after solving and plotting the percentage gain in CL/CD ratio relative to that of clean wing without the winglet against general angle of attack, for different cases where winglet cant angle was the only variation in geometrical parameters. Validation of the results was done by performing the grid independence and the convergence tests. The results were analyzed on the basis of relation of local angle of attack along the winglet span (αwinglet) with the general angle of attack (α). Near vertical winglets (lower cant angle) cases were found successful in maintaining zero pressure gradient at the tip, lowering the intensity of vortex and downwash intensity but a failure in harnessing the lift force like near horizontal winglets (highly canted winglet) and vice versa.